Quantum chemical calculations predict biological function: the case of T cell receptor interaction with a peptide/MHC class I - Antipas, Georgios S. E.; Germenis, Anastasios E. (Frontiers in Chemistry, 2015)
A combination of atomic correlation statistics and quantum chemical calculations are shown to predict biological function. In the present study, various antigenic peptide-Major Histocompatibility Complex (pMHC) ligands with near-identical stereochemistries, in complexation with the same T cell receptor (TCR), were found to consistently induce distinctly different quantum chemical behavior, directly dependent on the peptide’s electron spin density and intrinsically expressed by the protonation state of the peptide’s N-terminus. Furthermore, the cumulative coordination difference of any variant in respect to the native peptide was found to accurately reflect peptide biological function and immerges as the physical observable which is directly related to the immunological end-effect of pMHC-TCR interaction.